Efektivitas Media Cetak Leaflet dalam Peningkatan Pengetahuan Petani Padi Sawah (Oryza Sativa L.) di Desa Peatoa Kecamatan Loea Kabupaten Kolaka Timur - Erawati, Made Dwiyanty; Buana, Tjandra; Wunawarsih, Ima Astuty (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This study aims to find out the effectiveness of leaflet advertisement in improving knowledge of paddy farmers at Petaoa Village District of Loea East Kolaka. The respondent in this study was selected purposively and the number of respondents involved in this study consisted of two farmers workgroup. The first group was Samaturu’s paddy farmers’ workgroup, and the second group was Merta Agung paddy farmers’ working group. The design of the study was the pre-experimental design which applied one group pre-test post-test model. The study initially began with a (pre-test), treatment and then followed by a (post-test) in order to obtain accurate data for comparing the result of the research before and after treatment. Result of study showed that leaflet advertisement was effective in improving knowledge of paddy farmers for the Merta Agung group which is symbolized by the upright letters of Times New Roman font 12 in the amount of 56,25%. In the other hand, leaflet advertisement was not effective in improving knowledge of paddy farmers for Samaturu group which is symbolized by the upright letter of Times New Roman font 12 in the amount of 32.67%. The result of the study led to the conclusion that the effectiveness of leaflet advertisement remained two different results. It was effective for one paddy farmers workgroup, and also was ineffective for another one paddy farmers workgroup.